Exploring employee green behaviour in hospital settings: a scoping review protocol - Seung Eun Lee; Heejin Lim; Ja Kyung Seo (BMJ Open)
Introduction Hospitals have been identified as one of the drivers accelerating climate change, and in response, they have recently been incorporating environmentally sustainable goals into their organisations. Given the significant role that healthcare workers play in pursuing hospitals’ environmental goals through such actions as energy conservation and waste reduction, the scoping review is intended to comprehensively map and summarise the literature on these workers’ green behaviours within hospital settings.Methods and analysis The scoping review will follow Joanna Briggs Institute methodology and will report findings according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis extension for Scoping Reviews checklist. A comprehensive search for relevant sources published from database inception through 31 January 2025 will be conducted across seven electronic databases (PubMed, Cumulative Index of Nursing and Allied Health Literature, Embase, Scopus, Web of Science, PsycINFO and Emerald Journals), using key terms such as “hospital,” “healthcare workers” and “green behavior”. We will include peer-reviewed journal articles focusing on healthcare workers’ green behaviours in hospitals and relevant grey literature in order to provide an extensive review. Articles that are not written in English or that are intervention-based will be excluded. The study selection process will be presented in a flow diagram, and the text will summarise the findings of eligible studies according to key characteristics.Ethics and dissemination The scoping review will not require ethical approval. The findings will be disseminated through publication in a peer-reviewed journal and conference presentation.Trial registration number This protocol has been registered with the Open Science Framework (https://doi.org/10.17605/OSF.IO/YU345).